The Influence of Lifestyle and Product Features on Purchase Decisions for iPhone Products: (Study at State Polytechnic of Bengkalis) - Nia Rahmadhani; Nageeta Tara Rosa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine how much influence lifestyle and product features have on purchasing decisions on iPhone products at State Polytechnic of Bengkalis. This research uses quantitative methods using nonprobability purposive sampling. The sample size consisted of 100 respondents, and data processing using IBM SPSS version 26 with multiple linear regression analysis, including validity test, reliability test, T test, F test, and coefficient of determination (R2). The results of this study indicate that: (1) There is a positive and significant influence between lifestyle on purchasing decisions for iPhone products ( study at State Polytechnic of Bengkalis) with a T value of 3,807 with a significance of 0.000. (2) There is a positive and significant influence between product features on purchasing decisions for iPhone products (study at State Polytechnic of Bengkalis) with a value of 8,096 with a significance of 0.000. The coefficient of determination on the lifestyle variable on purchasing decisions for iPhone products (study at State Polytechnic of Bengkalis) is 12.9% and the product feature variable on purchasing decisions for iPhone products (study at State Polytechnic of Bengkalis) is 40.1%.